2023
DOI: 10.3390/healthcare11030366
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden in Informal Caregivers of Patients in Saudi Arabia Receiving Hemodialysis: A Mixed-Methods Study

Abstract: (1) Background: Long-term caregiving for patients receiving hemodialysis (HD), is associated with physical and psychological stress, which may impact on the well-being and quality of life of caregivers. Due to a lack of understanding of the experiences of informal caregivers of patients receiving HD, especially in Saudi Arabia, this study aimed to measure burden in informal caregivers of patients receiving HD, examine the factors that predict caregiver burden (CB), and explore the experience of burden in careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Approximately 73% of the study population reported experiencing some form of burden because of the care they provide for their family members. Our findings correlate with previous studies that show a high rate of depression, stigma and time burden among caregivers 13–15 17. We found significant levels of burden in caring for family members with serious memory disorders or mental retardation, which points to issues in terms of the ability to cope with the care demands.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Approximately 73% of the study population reported experiencing some form of burden because of the care they provide for their family members. Our findings correlate with previous studies that show a high rate of depression, stigma and time burden among caregivers 13–15 17. We found significant levels of burden in caring for family members with serious memory disorders or mental retardation, which points to issues in terms of the ability to cope with the care demands.…”
Section: Discussionsupporting
confidence: 90%
“…We found female gender to be significantly associated with a lower burden of caregiving. This is relevant to note as it is in contrast to previous studies that found female caregivers faced higher burdens and could be reasoned to reflect the influence of women’s perceptions of their roles and their reporting of the burden 11 14 15 17. This could also be due to the rapidly shifting social and gender dynamics in Saudi society and bears further study and exploration for potential self-reporting or social context issues 31…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These activities include tasks such as (a) assisting with acts of daily living and movement between a chair and bed; (b) transport, cooking meals, purchasing food and other supplies, cleaning, ensuring adherence to prescriptions, and coordinating external services; (c) making crucial treatment decisions for the individual; and (d) overseeing the financial aspects of their care. 33,34 Caregivers of individuals with chronic diseases shoulder a substantial emotional and financial responsibility that surpasses the general population’s experiences. Caregivers of individuals with chronic illnesses often experience higher levels of depression and exhibit elevated BMI scores compared to those who do not have caregiving responsibilities.…”
Section: Introductionmentioning
confidence: 99%